Kinetic patterns of dehydration of extracted raffinate of persimmon pulp - A. E. Makarov; A. H.-Kh. Nugmanov; I. Yu. Aleksanyan; P. D. Osmolovskiy; S. M. Arabov (Современная наука и инновации)
As a result of the conducted research, kinetic patterns of the drying process were obtained, which are necessary to determine the rational duration of dehydration and identify its mechanism based on the study of hygroscopic characteristics of raffinate crushed pulp of persimmon fruits. For crushed pulp of persimmon fruits, dewatering of raffinate is advisable to be carried out with convective supply of thermal energy by a heated air stream that moves orthogonally along the trajectory of the dried product. The above research results do not conflict with the results of other scientists, which makes it possible to use them in the engineering practice of the food industry in the design of plants for dehydration of plant products. It is noted that the dry raffinate from blanched persimmon contains a large proportion of dietary fiber and swelling capacity. The conducted studies allowed us to identify rational operating parameters of convective drying of fruit raffinate, namely: the speed of the drying agent equal to 2.5 m/s, its temperature 75 ° C and the filling level of the working space of the drum – 1/2 with a maximum theoretical productivity of Y =208 (kg / (m3· hour)). The temperature of the coolant differs from the final temperature of the product by 15-20 ° C, as a result of which the limiting temperature of the drying agent is assumed to be about 75 ° C, which is justified by experimental data at a higher temperature of the coolant relative to the recommended one in the article.